Differences In The Effect Of Motor Control Exercise And William Flexion Exercise On Pain In Low Back Pain Miogenic Patients At Ambalat Sesko Tni Clinic, Bandung - Siti Sarah Bintang; Karnirius Harefa; Sabirin Berampu; Dwi Handayani; Titin Novayanti Dey; Pratiwi Simarmata; MHD Yoppy (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Changes in the background needs and welfare of human life have led to a shift in modern lifestyle patterns. The growing population has resulted in increased work productivity, along with various types of work activities and a rise in complaints of symptoms like low back pain. Low back pain, or lower back pain, is a complaint where the pain can be local pain (inflammation) or radicular pain in the lower back. This pain can radiate to other areas, or the pain can be felt in the lower back, or it can be felt on a different side of the body from the center of the pain and can be felt in a variety of ways. Occupation is one of the factors causing LBP. Incorrect work postures, for example, sitting static for a long time and not using ergonomic sitting positions, are one of the factors in the occurrence of LBP (WHO, 2013). The purpose of this research is to find out if there is a comparison of the differences in the effect of motor control exercise and William flexion exercise on pain in myogenic low back pain patients at the Ambalat Sesko TNI Bandung clinic in 2023. The design in this study was a quasi-experiment with a control approach of two groups, pre-test and post-test, used to compare two independent groups, namely group I (motor control exercise) and group II (William flexion exercise). The research location was at the Ambalat clinic, Sesko TNI, with a total sample of 20 people. The research data was carried out using the normality test with the Shapiro-Wilk test. After the data was normally distributed, a hypothesis test was carried out using the independent paired sample t-test to obtain a p-value of 0.901 > (? = 0.05). The results of the analysis showed that the intervention of motor control exercise and William flexion exercise had the same effect on reducing pain, and there was no significant difference between giving myogenic low back pain at the Ambalat Sesko TNI Bandung clinic in 2023.